Gaelic and Identity: A Response to Iain MacKinnon. Issue 1 (February 2022) - Armstrong, Timothy Currie; McLeod, Wilson; Dunbar, Robert; Dunmore, Stuart; O'Rourke, Bernadette; Macleod, Michelle
Abstract : This article responds to the recent special issue of Scottish Affairs on 'Gàidhealtachd Futures' and in particular the article by Iain MacKinnon proposing that ancestry, ethnicity and indigeneity should become the principal elements in contemporary Gaelic identity. The editors of the special issue do not give an analytically meaningful presentation of the term Gàidhealtachd and MacKinnon fails to give a complete or balanced account of previous research on the question of Gaelic identity. There is considerable uncertainty about how the term Gael is understood today; many Gaelic speakers are reluctant to accept this label for themselves. MacKinnon's arguments concerning the role of ancestry in defining Gaelic identity are highly problematic in both analytical and political terms. His proposals concerning ethnicity and indigeneity are unsustainable, particularly in light of relevant legal standards, and amount to a strategic, ethical and legal dead end for the Gaelic revitalisation movement.